Towards a Sustainable Nepal: Assessing the Triple Bottom Line Awareness Among Young Generations - Rai, Arjun; Bhattarai, Mandip (Indonesian Journal Publisher, 2024)
Youth play a crucial role in advocating for social issues. Advocacy for a specific issue requires a thorough understanding of the issue. This study examined the youth’s awareness towards sustainable development using the Triple Bottom Line framework. In this study, the opinions of the youth were collected to determine how organisations can contribute to sustainable development, specifically in the areas of Profit (Economic Dimension), People (Social Dimension), and Planet (Environmental Dimension). The study used a cross-sectional research design. The study involves a non-vulnerable population. The Data was collected from the students pursuing higher education in Nepal. We collected responses from 142 university students through a structured questionnaire. The data were analyzed using factor analysis, descriptive statistics, and independent sample t-tests, stratified by gender and educational qualifications. The study’s findings indicated that youth showed the highest awareness in the social sustainability (People) dimension, followed by economic (Profit), and the least in environmental (Planet) sustainability. Likewise, the independent sample t-test results comparing mean differences across all dimensions of the Triple Bottom Line by gender showed insignificant differences in profit, people, and overall TBL dimensions. However, there was a significant mean difference in the level of concern about the planet or environment, with male students exhibiting higher awareness. The Study suggested statistically insignificant differences across all dimensions of the Triple Bottom Line and overall Triple Bottom Line due to differences in the educational qualifications of the students.